Study on Environmental Impact of Noise Generation Due to Operation of Wind Turbine Generators - Rajakumar, D. G.; Gowda, M. C. Mallikarjune; Babu, S. U. Suresh; Mounesh, G. K. (New Approaches in Engineering Research Vol. 2, 2021)
Power generation from wind energy has increased to a great extent in India during the recent past. The operation of Wind Turbine Generator (WTG) during power generation process generates noise of two types, one is mechanical noise and other one is Air cut noise. Any undesirable sound is considered as Noise. There are government regulations for the noise generation by any industry/personnel. The main aim of present paper is to reveal the range and impact of noise and its effect to the nearby dwellings considering a case study approach for the wind farm located in southern part of India. Study records the data related to noise level within and nearby the WTGs and measures it effect for day and night time for wind turbine located in Udumalaipet area of Coimbatore, Tamil Nadu India. Study uses both practical (on site data) and theoretical or standard noise level data prescribed by the Government of India to install any wind turbine generator near the dwellings. It also considers the important parameters like time and distance of measurement to assess the effect of noise considering different ratings of WTGs with different distance from them. Hence, it can be concluded that there is no issue of noise pollution to the neighboring society during the day and night time operation of WTG ratings of 0.85MW or 2 MW at different locations and are environmental friendly with their noise level within the acceptable level / zone prescribed by the Government authorities.